A REVIEW OF COASTAL DEFENSE MANAGEMENT TO SUPPORT NATIONAL RESILIENCE - Aris Tri Ika R; Moh. Kusaeni; Dhiana Puspitawati; Faishal Aminudin (Indonesian Naval Technology College STTAL, 2024)
The Surabaya Western Access Channel (SWAC) is a very congested, narrow channel but has several potentials for abundant natural resources. The problems in this Channel’s areThe busy traffic of both military and civilian ships passing through this channel has resulted in damage to several ecosystems and threatens fishery cultivation. Under the channel there are also dangerous objects for navigation such as shipwrecks that have not been lifted, many pipe installations and underwater cables. The level of shipping safety in SWAC is also relatively low. Therefore it is necessary to have shipping management, shipping safety, ecological maintenance, coastal community life and defense and security governance. The purpose of this paper is to review the existing conditions of coastal defense governance that have been implemented before. The method in this article is the VOSViewer analysis which analyzes the relationship between several keywords related to coastal defense management.